Regionalização como garantia de acesso aos serviços de saúde: revisão integrativa de literatura - Archangelo Junior, Antonio Flavio (2021)
This research is about the regionalization strategy of the Unified Health System with regard to access to health services. When looking at regionalization and its aspects that converge to access, the research outlines reflections on this understanding and can contribute to a better understanding, or even, to motivate the production of new research. Through an integrative review of studies produced between 2015 and 2020, twelve articles were selected to analyze in which aspects regionalization converged (or not) with access. Under this lens, central axes such as direct to health, financing and territorial organization were detected, detecting the existence of assertive gaps in how regionalization is related to access. Within the character of application in professional practice, it is concluded that the change of focus depends on the adoption of a new paradigm that involves a process of “empowered regionalization” that is transparent and collaborative between all the actors involved.